High involvement product information search on the internet among consumers in Yinchuan, China - Zhu, Beiyu (2016)
Consumers are armed with the most efficient ways to get information on product specifications, stores, and promotions due to the advance of the Internet. In China, consumers have increasingly depended on the Internet for pre-purchase information searching, especially for high involvement products. However, the extant research has only offered limited information on online information search behaviour for high involvement products among consumers in China and deficient findings. Therefore, this study focused on examining the extent and patterns of information search using the Internet for high involvement product among consumers in Yinchuan, China. This study also examined the predictors of information search on the Internet and mediating effect of motivation to search on the Internet on the relationships between the selected predictors and information search on the Internet. Based on this, a conceptual model to determine the relationships between the selected predictors (perceived search cost, product involvement, perceived risk, extent of offline information usage, product knowledge, information quality, system quality, and service quality) and information search on the Internet mediated by motivation to search was developed. This is quantitative study, in which 402 consumers of automobile were selected using stratified sampling technique. They were selected from the local automobile administrative bureaus while applying for license plates. Data were collected using the self-administrated questionnaire and 390 valid responses were used for data analysis. SPSS and AMOS software were used for data analysis. Descriptive analysis, cluster analysis, and structural equation modeling were employed to analyze the data. The results of descriptive analysis of this study showed that, in general, consumers in Yinchuan of China conducted moderate extent search on the Internet for high involvement product information. Specifically, retailers and manufacturers’ websites, other consumers’ online reviews, and ratings were the online sources that consumers consulted to a greater extent for information. A two-stage cluster analysis further revealed that the heterogeneous respondents were composed of four homogeneous subgroups, which were the low search cluster (31.0%), selective search cluster (36.4%), moderate search cluster (18.5%), and high search cluster (14.1%). Consumer’s age and experience with the Internet were found to be associated with the cluster membership of online information search. The analysis of SEM revealed an acceptable fitness between the proposed model and the data, which indicated the significant contribution of perceived risk, extent of offline information usage, information quality, and service quality to information search on the Internet. SEM also revealed that utilitarian motivation to search on the Internet was mediating the relationships between perceived search cost, product involvement, perceived risk, and information search on the Internet. Based on the findings, it could be concluded that consumers in Yinchuan of China conducted moderate information search on the Internet; they were differentiated in terms of their online search behaviour; the integration of perceived risk, extent of offline information usage, information quality, and service quality functioned to regulate information search on the Internet; and utilitarian motivation to search mediated the relationships between perceived search cost, product involvement, perceived risk, and information search on the Internet. This study supports the importance of unique characteristics of the Internet in understanding information search behaviour among consumers.